The Influence of E-WOM, Hedonic Shopping, Sales Promotion, and FOMO on Glad2Glow at Shopee - Saputri, Dinda Indah; Randikaparsa, Irawan; Astuti, Herni Justiana; Bagis, Fatmah (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2026)
This study examines the effect of Electronic Word of Mouth (E-WOM), Hedonic Shopping, Sales Promotion, and Fear of Missing Out (FOMO) on impulse buying of Glad2Glow products on Shopee. A quantitative approach was employed using a survey of 333 students of Universitas Muhammadiyah Purwokerto, analyzed through PLS-SEM. The results indicate that all variables simultaneously affect impulse buying. Partially, E-WOM has no significant effect, while Hedonic Shopping, Sales Promotion, and FOMO show positive and significant effects. These findings suggest that impulse buying is driven more by emotional and situational factors than by online review information. This research is expected to contribute to business actors in designing more effective marketing strategies on digital platforms.